2007
DOI: 10.1002/eji.200636938
|View full text |Cite
|
Sign up to set email alerts
|

Non‐myeloablative mixed chimerism approaches and tolerance, a split decision

Abstract: Stable mixed chimerism has been considered the most robust tolerance strategy. However, rejection of solid donor tissues by chimeras has been observed, a state termed split tolerance. Since new non-myeloablative mixed chimerism approaches are being actively pursued, we sought to determine whether they lead to full tolerance or split tolerance and to define the mechanisms involved. Fully mismatched mixed chimeras generated by induction with various lymphocyte-depleting antibodies along with either low-dose irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 56 publications
(81 reference statements)
1
38
0
1
Order By: Relevance
“…However, it is clear that even with chimerism, whether induced naturally or otherwise (6 -11), it is possible for donor tissues to be rejected (known as "split tolerance"). We recently confirmed and extended this observation to murine chimeras generated by more than one clinically relevant protocol (12). Importantly, split tolerance appears to be possible in mixed chimeras (10 -12) that are more clinically favored than full chimeras.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…However, it is clear that even with chimerism, whether induced naturally or otherwise (6 -11), it is possible for donor tissues to be rejected (known as "split tolerance"). We recently confirmed and extended this observation to murine chimeras generated by more than one clinically relevant protocol (12). Importantly, split tolerance appears to be possible in mixed chimeras (10 -12) that are more clinically favored than full chimeras.…”
mentioning
confidence: 58%
“…Importantly, split tolerance appears to be possible in mixed chimeras (10 -12) that are more clinically favored than full chimeras. Most past studies demonstrated split tolerance in chimeras that maintained donor hematopoietic cells but rejected donor skin transplants, the cause of which was likely immunity toward polymorphic tissue-specific Ags expressed by donor skin but absent from their bone marrow cells (10,(12)(13)(14)(15)(16)(17)(18). Although split tolerance involving tissues other than skin has not often been reported in murine chimeras, in a canine model split tolerance was observed in which chimeric recipients rejected donor hearts (19).…”
mentioning
confidence: 99%
“…In a previous study, C57BL/6 mice treated with a similar protocol using 20 mg/kg Bu, T cell-depleting antibodies and transplanted with full-mismatched BALB/c WBM, followed by 14-day SIR immunosuppression, showed stable chimerism but nevertheless rejected donor skin grafts (37). Using a more clinically realistic donor-recipient strain combination, we found that decreasing the Bu dose to 10 mg/kg and increasing the SIR course to 28 days could efficiently establish long-term allogeneic tolerance to donor skin graft and hematopoietic antigens in 100% of mice.…”
Section: Discussionmentioning
confidence: 95%
“…Bu is typically administered at a dose of 20 mg/kg or higher, with higher levels of chimerism corresponding to dosage increases (6,36,37), as mice are relatively more resistant to Bu than humans. We found that 10 mg/kg Bu was sufficient to deplete LSK progenitors without severely affecting WBM cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Increased regulatory activity might thus also provide a potential solution for the phenomenon of "split tolerance" seen in some chimeras, in which some types of grafts (e.g., BM) are accepted while other types (e.g., skin or heart) are rejected [20,72]. Tissuespecific minor antigens that have been identified to cause split tolerance in several models [73,74], are now known to be amenable to active regulation [20,41]. Thus, deliberately shifting the contributing mechanisms toward regulation indeed appears beneficial for the robustness of the state of tolerance achieved through mixed chimerism and increases the efficacy of such protocols.…”
mentioning
confidence: 99%